PENERAPAN INSTRUKSI PADA TAHAP DISCUSSION MODEL PEMBELAJARAN GUIDED INQUIRY UNTUK MENINGKATKAN KEMAMPUAN MENEMUKAN DAN MENGHUBUNGKAN KONSEP - Ade Raya Anggriyani (Biogenesis, 2018)
ABSTRACT The research aims to improve the ability of student’s find and connect concepts through implementation of instruction in discussion phase guided inquiry learning. The research is a classroom action research with 2 cycles. The research procedure includes stages planning, acting, observing, and reflecting. Subjects of this research are Senior High School students consist of 10 male and 22 female. Data collected with observation, interview, documentation, and test for measure score of concept map’s students. The data validation used triangulation method. The analyzed data technique were using qualitative-descrptive with stages data reduction, data display, and drawing inference. The result of the research showed score of concept map in the pre-cycle have range 3,1%-10,8% and average score 6,7% with 50%  students above the average. Score of concept map in the cycle I have range 6,8%-34,8% and average score 14,6% with 35,4% students above the average. Score of concept map in the cycle II have range 7,9%-42,9% and average score 15,6% with 27,5%  students above the average, thus the ability of student’s find and connecting conceptwas improved by the range and average score of concept map from pre-cycle to cycle II. Keywords:  instruction, discussion, guided inquiry, find concept, connect concept